Dampak Pandemi Covid-19 Terhadap Pengelolaan Kas Bendahara Penerimaan Pemerintah Daerah - Muhammad Heru Akhmadi; Arda Octaviola Rachmalia (JIAP (Jurnal Ilmu Administrasi Publik), 2021)
:  Cash is an important instrument for a company. The company’s financial performance can be judged by how the company's cash is managed. During the Covid-19 pandemic in 2020, the government decided to close tourist attractions. This study aims to find out how the performance of cash management during the Covid-19 pandemic was carried out by the Revenue Treasurer at the Pati Regency Youth Sports and Tourism Office. This study uses a descriptive qualitative method to analyze the cash management process in the Revenue Treasurer such as planning, recording, to depositing cash into local government accounts. Data were collected by interview and literature study. The results showed that in general, the Revenue Treasurer has managed cash well, starting from cash planning, recording, to depositing cash. However, the Covid-19 pandemic in 2020 has caused the number of regional revenues from the tourism sector to decline significantly. Some of the obstacles of the Revenue Treasurer in carrying out the cash receipt are the existence of multiple positions, weak communication, and the limited number of collecting officers at tourist attractions. Furthermore, the Revenue Treasurer keeps consistently recording as well as the period of cash is received. the Revenue Treasurer deposited the cash into the regional treasury account on the same day as cash is received. There were evidence of cash deposit in the form of a Deposit Certificate which has been validated by a partner bank appointed by the regional government.